The impact of liraglutide treatment on erectile function of the diabetic rats - Gönültaş, Serkan; Tüken, Murat; Çulha, Mehmet Gökhan; Sulejman, Suhejb; Tavukçu, Hasan Hüseyin; Bastug, Yavuz; Serefoglu, Ege Can; Semerciöz, Atilla (The European Research Journal, 2023)
Objectives: Glucagon like peptide-1 (GLP-1) is a hormone released from intestinal L-cells following nutrient consumption. It potentiates secretion of insulin from pancreatic beta-cells thus GLP-1 analogues are used for the treatment of type-2 diabetes mellitus( T2DM). This study aims to evaluate impact of GLP-1 receptor agonist liraglutide on erectile function of diabetic rats. Methods: Male Sprague-Dawley rats (n = 30, 13-weeks old, 240-335 gr) were fed with fatty diet for 2-weeks and divided into 3 groups (n = 10 each). The rats in the first group served as controls (Group C) whereas the rats in the remaining two groups were injected with streptozocin and became T2DM for forming diabetic group (Group D) and treatment group (Group DT). Rats in group D received citrate buffer injections whereas rats in the group DT received liraglutide injections (0.3 mg/kg/12h) subcutaneously. Erectile functions of all rats were evaluated with intracavernosal pressure (ICP)/mean arterial pressure (MAP) measurements. Moreover, plasma sex hormone levels (Testosterone, FSH, LH) were measured and histological assessment of midpenile tissue were performed (Collagen-Type-IV, rat epithelial antigen-1, nNOS). Results: Maximum ICP/MAP ratios were 0.790 ± 0.164, 0.263 ± 0.139 and 0.652 ± 0.131 in Group C, Group D and Group DT. Although mean ICP/MAP ratios were similar in Group C and Group DT (p = 0.076), mean ICP/MAP ratio was significantly lower in Group D (p < 0.001). Testosterone and FSH results were significantly lower in the Group D as well (p = 0.001). Histological analyses revealed that nNOS (p < 0.001), rat epithelial antigen-1 (p = 0.016) and muscle/collagen ratio (p = 0.015) were also lower in Group D, compared with the other groups. Conclusions: GLP-1 receptor agonist liraglutide demonstrated protective effects on the erectile tissues of the diabetic rats. Clinical trials are required to confirm if liraglutide treatment has similar beneficial effects on men who have T2DM.